If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f + 43 = 120 Reorder the terms: 43 + f = 120 Solving 43 + f = 120 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-43' to each side of the equation. 43 + -43 + f = 120 + -43 Combine like terms: 43 + -43 = 0 0 + f = 120 + -43 f = 120 + -43 Combine like terms: 120 + -43 = 77 f = 77 Simplifying f = 77
| 6n+21=4n+1 | | e-35=27 | | 0.000054s= | | d+19=83 | | k^2-36= | | f+27=49 | | 26/100= | | 0.10(y-8)+0.18y=0.12y-0.03(40) | | 3x^2+5x+k= | | 5+d=71 | | I=(1535)(.045)(3) | | 0.50x+0.80(60)=0.25(116) | | -20-40=-21/4 | | -40x+5y=30 | | -40=-21/4(x-20) | | (x-3/2)^2 | | -40=-21/4(x-20 | | x/3+2x/9+4x/27+8x/81+1=x | | 5p+(-6)= | | -sin(6x)=0 | | 3n^3/n^3 | | (-2r)(8)+(25)= | | 4/2-4/5= | | 9=8m+9 | | -3(-4-6y)+7(-4+5)=-8 | | 4/21*(145-y) | | X+(-4)+6x=3x+(-1)+5 | | 5-(x+7)=5x-8 | | 3+(y+2)+2(y-3)=-15 | | -3x=7-13 | | 4+ln(x+3)=6 | | 15=3r-6 |